Evaluasi Program Latihan Dasar Kepeminpinan Siswa: Analisis Efektivitas, Biaya dan Manfaat - Kurniasari, Murni (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This research explores the effectiveness, costs, and benefits of the Basic Leadership Training Program at SMP Islam Raden Patah. Using a descriptive qualitative approach, the study evaluates the program's impact on participants, school staff, and the educational environment. Informants include students enrolled in the program, instructors, and school staff. Data collection techniques involve in-depth interviews, observations, and document analysis. Qualitative data analysis employs the reduction, presentation, and conclusion-drawing processes. The research findings indicate the success of the Basic Leadership Training Program (PLDK) at SMP Islam Raden Patah. The effectiveness analysis highlights improvements in students' leadership skills, positive changes in attitudes, and increased knowledge of leadership concepts. Cost evaluation reveals significant investments in instructors, facilities, and human resources, with potential long-term economic impacts. Benefit analysis emphasizes the program's contributions to academic achievements, positive behavioral changes, and the creation of an inclusive school atmosphere. Recommendations for program development and long-term monitoring are outlined as the foundation for sustaining PLDK in the future.